Total economic value of marine ecosystem service in Malaysia: a review / Wan Nur Ayuni Wan Ab Rashid, Junainah Mohamad and Mohd Azhar Hamzah - Wan Ab Rashid, Wan Nur Ayuni; Mohamad, Junainah; Hamzah, Mohd Azhar (UiTM Press, 2024)
The marine ecosystem service in Malaysia offers wealth benefits, including fisheries resources, ecotourism, coastal protection, climate regulation, and nutrient recycling. However, the failure to impute the price of ecosystem services (ES) in marine ecosystem service would result in a misguided policy, and society would be detrimental as a result of the misallocation of resources. The full potential of these services has not been fully quantified in economic terms. This paper reviews the suitable indicators pertinent to a Total Economic Value (TEV) of marine ecosystem service to propose a conceptual framework for the TEV of marine ecosystem service in Malaysia. We conduct a comprehensive review of the marine ecosystem service components (2018–2023) of literature. Studies are categorised based on the TEV and ES components they refer to, as well as the different approaches to the use of ecosystems. This review aims to establish a standard for future research on the TEV of marine ecosystem services, as there is a lack of studies on this topic, and to raise community awareness of the value of protecting natural resources, inform policymakers, and aid in cost-benefit assessments of initiatives. The data will help demonstrate the benefits of protecting marine ecosystem services.